Tell no lies [large type] - Brennan, Allison (Brennan, Allison. Quinn & Costa thriller, 2023)
"The unsolved murder of a young activist leads to the discovery of much darker crimes in New York Times bestselling author Allison Brennan's latest compelling thriller to feature the young, edgy detective Kara Quinn and the loner FBI agent Matt Costa. This time they work to uncover possible ties to a high-stakes cartel in the Southwest desert. Something mysterious is killing the wildlife in the mountains just south of Tucson. When a college intern turned activist sets out to collect her own evidence, she, too, ends up dead. Local law enforcement is slow to get involved. That's when the mobile FBI unit goes undercover to infiltrate the town and its copper refinery in search of possible leads. Quinn and Costa find themselves scouring the desolate landscape, which keeps revealing clues to something much darker--greed, child trafficking and more death. As the body count adds up, it's clear they have stumbled onto much more than they bargained for. Now they must figure out who is at the heart of this mayhem and stop them before more innocent lives are lost"--